Characterization and acetone gas sensing properties of electrospun TiO2 nanorods. (May 2015) - Bian, Haiqin; Ma, Shuyi; Sun, Aimin; Xu, Xiaoli; Yang, Guijin; Gao, Jiming; Zhang, Zhengmei; Zhu, Haibin
Highlights: Electrospinning synthesized TiO2 were composed of uniform and long nanorods. There are two emission peaks at 401 and 467 nm in PL spectra. TiO2 nanorods based sensor has good stability and selectivity for acetone. The sensing mechanism is discussed in detail. Abstract: In this work, random network structure of titanium dioxides (TiO2 ) nanorods was synthesized by calcining electrospun TiO2 /PVP hybrid rods. Structural, optical and acetone gas sensing properties of the nanorods were investigated. The TiO2 nanorods are polycrystalline with a mixture of anatase and rutile structures. The diameter of TiO2 nanorods is about 500 nm. The photoluminescence (PL) spectra measurement at room temperature revealed that a broad emission band including the two emission peaks are about at 401 and 467 nm. The sensor shows the high response, good reproducibility and selectivity for acetone (CH3 COCH) with a fast response and recovery time at 500 °C. In addition, the acetone sensing mechanism of the TiO2 nanorods sensors is discussed.